AQbD-based stability indicating development and validation of azilsartan medoxomil and cilnidipine by UPLC method - Swarupa Bandi, Sreedevi Adikay (Journal of Applied Pharmaceutical Science, 2023)
This work describes a chromatographic technique for quantifying azilsartan medoxomil (AZL) and cilnidipine (CIL) in bulk and pharmaceutical formulations using quality by design (QbD). The analytical targeting profile distribution and critical analytical attributes (CAA) are incorporated with analytical QbD. Risk evaluation studies and factor screening research facilitate the identification of critical method parameters (CMPs). The application of 22 full factorial designs was used to optimize the process. Selected CMPs, such as plate number of peak 1 (R1), resolution (R2), and tailing factor of peak 2 (R3) were evaluated. Utilizing statistical data and response surface plots, the individual and interaction effects of CMP on CAA were evaluated. The significance (p ? 0.05) of the procedure parameters was shown by analysis of variance. Mobile phase-Acetonitrile and 1% triethylamine buffer (50:50 v/v), pH (2.5) adjusted with 0.1% ortho-phosphoric acid, and Waters X-Bridge C18 column, (50 × 4.6 mm, 2.5 μm), the flow rate is 0.5 ml/minute with photodiode array detector at 273 nm. According to ICH requirements, method validation and subsequent stress degradation experiments were carried out. All variables are within their bounds. The suggested method is effectively illustrated by using a QbD to perform extremely sensitive, stable, and suited for regular analysis and clinical applications.